Myth as Ritual Foundation: A Semiotic Analysis of the Mayadenawa Narrative in Balinese Religious Practice - Ni Luh Sutjiati Beratha; Desak Putu Eka Pratiwi; Ni Ketut Puji Astiti Laksmi (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This article examines the Mayadenawa myth as a semiotic foundation of Balinese Hindu ritual, with particular attention to the Galungan festival. Galungan is a major religious celebration held every 210 days in Bali to commemorate the victory of dharma (cosmic order) over adharma (disorder) and to mark the return of ancestral spirits to the human realm. Employing Barthes’ theory of two-order signification, this study analyzes the Mayadenawa narrative at the levels of denotation, connotation, and myth. The findings show that the myth functions not merely as a narrative of divine conflict, but as a cultural sign system that legitimizes ritual practice and naturalizes moral and religious values. By applying a semiotic approach, this study moves beyond descriptive interpretations and demonstrates how myth operates ideologically to sustain Balinese Hindu identity through rituals.